International Student Projects in a Blended Setting: How to Facilitate Problem Based Project Work - Pedersen, Jens Myrup; Elsner, Raphael; Kuran, Mehmet Şükrü; Prikulis, Lauris; Zabłudowski, Łukasz; Zabludowski, Lukasz (University of Minho, 2018)
This paper describes our experiences with facilitating international student projects during three years of the Erasmus+ Strategic Partnership COLIBRI (Collaboration and Innovation for Better, Personalized and IT-Supported Teaching). Each year 7-8 student projects were carried out in groups of 3-5 students from different European universities, with different backgrounds from business and engineering. Each year new students were selected for participation. The student projects carried out were based on real-life problems from companies, and each group was assigned both an academic supervisor from one of the seven participating universities and an academic supervisor from one of the three participating companies. The projects were based on a combination of physical mobility and virtual mobility: The students would meet for one week at the beginning of the project work, then work together virtually for around 2-3 months, and then meet again for a week where the projects were finalised and evaluated. This setup is challenging: The students do not know each other beforehand, most of the students are not familiar with problem based projects and collaboration with industry, the students represent both different educational traditions and disciplines, and the virtual collaboration is by itself challenging. The project was carried out in three cycles, where for each cycle we systematically evaluated the previous experience and adapted our approach to e.g. project descriptions, seminar organisations, elements to support the students in the project work, and project supervision. Based on our evaluations, we see that each year student satisfaction was increased, and at the same time both companies and students reported improved learning outcome and project results. The last year a survey was made for the students to evaluate the support from different elements such as online modules, introduction to project work, instructions of expected outcome, templates, and supervision during both physical and virtual collaboration phases. We conclude that such international and interdisciplinary projects can be very rewarding, but also that careful planning and implementation is needed to achieve the full potential. © 2018 Elsevier B.V., All rights reserved.
Keywords: Collaboration; Interdisciplinary; Internationalisation; Problem Based Learning